2020
DOI: 10.1039/d0ma00494d
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic tungstate nanoparticle-decorated-lignin electrodes for flexible supercapacitors

Abstract: Bimetallic tungstates (M2M1WO4; M= transition metal) are promising candidates for electrochemical energy applications. However, the effects of the secondary metal (M2) on the pseudocapacitance behavior of bimetallic tungstates are not...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 58 publications
2
11
0
Order By: Relevance
“…Similarly, the diffraction peaks positioned at 23.8, 30.6, 36.2, 41.2, 53.9, and 63.8° (Figure S5) align well with (−110), (−111), (200), (−201), (−202), and (222) of CoWO 4 (JCPDS no. 015-0867) . For the proposed core–shell, ZNM@CW, the peaks (in Figure ) are in good accordance with the individual materials α and β-NiMoO 4 and CoWO 4 , verifying the successful formation of ZNM@CW.…”
Section: Results and Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Similarly, the diffraction peaks positioned at 23.8, 30.6, 36.2, 41.2, 53.9, and 63.8° (Figure S5) align well with (−110), (−111), (200), (−201), (−202), and (222) of CoWO 4 (JCPDS no. 015-0867) . For the proposed core–shell, ZNM@CW, the peaks (in Figure ) are in good accordance with the individual materials α and β-NiMoO 4 and CoWO 4 , verifying the successful formation of ZNM@CW.…”
Section: Results and Discussionsupporting
confidence: 57%
“…015-0867). 41 For the proposed core−shell, ZNM@ CW, the peaks (in Figure 8) are in good accordance with the individual materials α and β-NiMoO 4 and CoWO 4 , verifying the successful formation of ZNM@CW. Interestingly, with the introduction of the CW shell (see Figure 8), β-NiMoO 4 has become more prominent, which qualifies for energy storage applications.…”
Section: Physiochemical Characterization Of the Prepared Materialssupporting
confidence: 60%
“…The ability to attain relatively high pseudocapacitive performance, arising from their many valence state transitions, is key to their electrochemical characteristics [ 59 ]. Combining lignin with metal oxides can improve the electrochemical characteristics of electrodes [ 60 , 61 , 62 , 63 , 64 ]. Incorporating lignin into metal oxides for supercapacitor applications has proven challenging, due to difficulties in regulating the resulting electrochemical properties, with significant impacts on the cycle life and performance of the devices.…”
Section: Fundamentals Of Ligninmentioning
confidence: 99%
“…A supercapacitor fabricated using an Al/lignin–NiWO 4 anode, an Al/AC cathode, and PVA/H 3 PO 4 as the gel electrolyte had a specific capacitance of 17.01 mF cm −2 at 0.13 A g −1 , good stability (84% capacitance retention after 2000 cycles), a maximum energy density of 2 W h cm –2 , and a maximum power density of 100 W cm −2 . Jha et al also prepared NiCoWO 4 -decorated lignin electrodes for flexible supercapacitors and investigated the effect of Ni as a secondary metal on pseudocapacitance of NiCoWO 4 [ 60 ]. Electrochemical testing of the lignin/NiCoWO 4 /AC- and lignin/CoWO 4 /AC-based supercapacitors revealed that the specific capacitance of the bimetallic tungstate (NiCoWO 4 )-containing supercapacitor (862.26 mF cm −2 ) was 141 times higher than that of the monometallic tungstate (CoWO 4 )-containing supercapacitor.…”
Section: Fundamentals Of Ligninmentioning
confidence: 99%
“…[4,25,26] In a recent article, Swarn et al prepared cobalt tungsten acid salt (CoWO 4 ) to modify lignin as a supercapacitor electrode material, which exhibited a power density of up to 5.75 Wh kg À 1 . [27] Geneva et al fabricated a Co 3 O 4 aerogel using epoxy compounds driven by condensation polymerization, then applied it as an electrode material for supercapacitors with specific capacitance up to 550 F g À 1 . [28] Incomplete hydrogels were readily formed using a condensation polymerization process.…”
Section: Introductionmentioning
confidence: 99%